Aromatic C–H amination: a radical approach for adding new functions into biology- and materials-oriented aromatics. Issue 29 (6th July 2017) - Murakami, Kei; Perry, Gregory J. P.; Itami, Kenichiro
Abstract : Recent developments in the radical C–H amination of biology- and materials-oriented aromatics are summarized in this perspective. Abstract : C–H amination is the most powerful method to directly add nitrogen functionalities into a variety of arenes including biology- and materials-oriented molecules. Recent developments in aromatic C–H amination chemistry have enabled the conversion of unactivated arenes into a range of arylamine derivatives without using directing groups or excess amounts of arenes. The key for such successful transformations is the catalytic generation of nitrogen or arene radical intermediates. In this perspective, we discuss recent developments in the radical C–H amination of aromatic molecules. We believe the resulting arylamines, which are hitherto difficult to access, will exhibit unexplored functions for biological and materials application.